Atmospheric histories and global emissions of halons H‐1211 (CBrClF2), H‐1301 (CBrF3), and H‐2402 (CBrF2CBrF2). Issue 7 (14th April 2016) - Vollmer, Martin K.; Mühle, Jens; Trudinger, Cathy M.; Rigby, Matthew; Montzka, Stephen A.; Harth, Christina M.; Miller, Benjamin R.; Henne, Stephan; Krummel, Paul B.; Hall, Bradley D.; Young, Dickon; Kim, Jooil; et al.
Abstract: We report ground‐based atmospheric measurements and emission estimates for the halons H‐1211 (CBrClF2 ), H‐1301 (CBrF3 ), and H‐2402 (CBrF2 CBrF2 ) from the AGAGE (Advanced Global Atmospheric Gases Experiment) and the National Oceanic and Atmospheric Administration global networks. We also include results from archived air samples in canisters and from polar firn in both hemispheres, thereby deriving an atmospheric record of nearly nine decades (1930s to present). All three halons were absent from the atmosphere until ∼1970, when their atmospheric burdens started to increase rapidly. In recent years H‐1211 and H‐2402 mole fractions have been declining, but H‐1301 has continued to grow. High‐frequency observations show continuing emissions of H‐1211 and H‐1301 near most AGAGE sites. For H‐2402 the only emissions detected were derived from the region surrounding the Sea of Japan/East Sea. Based on our observations, we derive global emissions using two different inversion approaches. Emissions for H‐1211 declined from a peak of 11 kt yr −1 (late 1990s) to 3.9 kt yr −1 at the end of our record (mean of 2013–2015), for H‐1301 from 5.4 kt yr −1 (late 1980s) to 1.6 kt yr −1, and for H‐2402 from 1.8 kt yr −1 (late 1980s) to 0.38 kt yr −1 . Yearly summed halon emissions have decreased substantially; nevertheless, since 2000 they have accounted for ∼30% of the emissions of all major anthropogenic ozone depletion substances, when weighted by ozone depletion potentials. Key Points: Halon measurements were combined from two large networks and from air archives Complete atmospheric histories for these halons are reported for both hemispheres Complete global emission estimates and a regional H‐2402 emission pattern are reported on